Analisis Penerapan Laporan Keuangan Dalam Pengembangan Kewirausahaan Pada Usaha Dinarban Kota Palembang - Puspa Djuita; Andini Utari Putri; Hendra Musa (Jurnal Ilmiah Ekonomi Global Masa Kini, 2023)
In this research, it was conducted at the Palembang City Dinarban Business. The type and source of data in this study is qualitative data using secondary data, namely by making observations or observations and documentation in the form of records of production costs needed to calculate sales and purchases in 2022. The financial statements themselves are very important for business continuity in order to find out how much the profits earned and how in the future to treat these profits which can be used as business capital in the next period. Dinarban Enterprises in preparing accounting reports have not prepared a financial position report, this is because Dinarban Enterprises do not understand and are confused about preparing financial reports in accordance with applicable standards. This business also does not take into account assets and liabilities & equity clearly and accurately, and does not take into account the assets owned by DinarBan. The main obstacle is because even though business owners are aware that proper and correct financial reports are important for the continuity of the business being carried out, however, this is considered complicated or troublesome and also a lack of understanding of the business. In addition, the level of education also affects understanding in making financial reports. Therefore, financial reports can be a reference for making a decision. So that it can make it easier for you to run a business. The results of these financial reports can be used as a decision-making tool. Therefore, the authors provide advice for Dinarban Enterprises to implement recording using Financial Reports in accordance with existing accounting standards to make it easier for business owners to make decisions accurately in accordance with business conditions. Keywords: Financial Statements, Entrepreneurship.